Implikatur Wacana Humor dalam Webtoon â€œTahi Lalatsâ€ Karya Nurfadli Mursyid - Sri Juniati (STKIP Paris Barantai, 2019)
The formulation of the problem in this study is (1) What is the meaning of implicature in humorous discourse webtoon